Carfilzomib Mitigates Lipopolysaccharide/D-Galactosamine/Dimethylsulfoxide-Induced Acute Liver Failure in Mice - Dhafer Y. Alhareth; Abdulrazaq Alanazi; Wael A. Alanazi; Mushtaq A. Ansari; Mahmoud N. Nagi; Sheikh F. Ahmad; Mohamed S. M. Attia; Ahmed Nadeem; Saleh A. Bakheet; Sabry M. Attia (Biomedicines, 2023)
Acute liver failure (ALF) is a disease accompanied by severe liver inflammation. No effective therapy is available yet apart from liver transplantation; therefore, developing novel treatments for ALF is urgently required. Inflammatory mediators released by NF-кB activation play an essential role in ALF. Proteasome inhibitors have many medical uses, such as reducing inflammation and NF-кB inhibition, which are believed to account for most of their repurposing effects. This study was undertaken to explore the possible protective effects and the underlying mechanisms of carfilzomib, a proteasome inhibitor, in a mouse model of ALF induced by lipopolysaccharide/D-galactosamine/dimethylsulfoxide (LPS/GalN/DMSO). Carfilzomib dose-dependently protected mice from LPS/GalN/DMSO-induced liver injury, as indicated by the decrease in serum alanine aminotransferase and aspartate aminotransferase levels. LPS/GalN/DMSO increased TNF-α, NF-кB, lipid peroxidation, NO, iNOS, cyclooxygenase-II, myeloperoxidase, and caspase-3 levels. Carfilzomib administration mitigated LPS/GalN/DMSO-induced liver damage by decreasing the elevated levels of TNF-α, NF-кB, lipid peroxidation, nitric oxide, iNOS, cyclooxygenase-II, myeloperoxidase, caspase-3, and histopathological changes. A restored glutathione level was also observed in the carfilzomib-treated LPS/GalN/DMSO mice. Our results demonstrate that carfilzomib protects against LPS/GalN/DMSO-induced ALF by inhibiting NF-кB, decreasing inflammatory mediators, oxidative/nitrosative stress, neutrophil recruitment, and apoptosis, suggesting that carfilzomib may be a potential therapeutic agent for ALF.